Are national climate change mitigation pledges shaped by citizens' climate action preferences? Evidence from globally representative data - Heinz Welsch (University of Oldenburg, Department of Economics, 2024)
The Paris Agreement on Climate Change requests signatory countries to specify voluntary caps on their greenhouse gas emissions. The caps stated by the end of 2021 imply percentage emission reductions that vary widely across countries. This paper uses globally representative data from the Global Climate Change Survey to study how countries' emission reduction pledges are related to climate action preferences of their respective citizens. The study finds the following: (1) Nations' percentage reduction pledges (PRPs) are not significantly related to citizens' mean national willingness to contribute (WTC) to climate change mitigation. (2) WTC and PRPs are linked to key country characteristics in diametrically opposite ways. Specifically, (2a) WTC is positively related to average annual temperatures and negatively related to per-capita income and per-capita emissions, whereas (2b) PRPs are negatively related to average annual temperature and positively related to percapita income and per-capita emissions. (3) Measures of divergence between PRPs and WTC are negatively related to citizens' satisfaction with democracy. Assuming that temperatures, per-capita income, and per-capita emissions indicate sensitivity to climate change, adaptive capacity, and mitigation costs, respectively, finding (2a) is consistent with standard cost-benefit considerations. Assuming that per-capita emissions and per-capita income indicate "Differentiated Responsibilities and Respective Capabilities", finding (2b) is consistent with ethical principles of equity and fairness. Considering right-wing populists' using climate change as a political battleground, finding (3) suggests the possibility that ambitious mitigation targets may backfire by fuelling support for anticlimate populist parties - a political- economy tragedy of the commons.
Keywords: Q54; D61; D63; D72; 330; Paris Agreement pledges; climate action preference; willingness to contribute; costbenefit calculus; climate ethics; satisfaction with democracy